Paediatric Stroke: Diagnostic Strategies and Therapeutic Dillemas - Bieszczad, Dominika; Barczewska, Magdalena; Mazurek, Adam; Popielarska, Kinga; Opalińska-Kubowicz, Marta; Musialska, Zuzanna; Prostenko, Yuliia; Kowalska, Marta; Marczak, Anna; Stadnicka, Olga; et al. (Journal of Education, Health and Sport, 2026)
Background. Paediatric arterial ischemic stroke is a potentially disabling neurological condition that remains underrecognized due to its rarity and atypical clinical presentation. Diagnosis in children is often delayed because of heterogeneous symptoms and differences in stroke mechanisms compared with adults. Despite advances in neuroimaging and acute reperfusion therapies, evidence-based paediatric-specific diagnostic and treatment strategies remain limited. Aim. This review aimed to summarise current evidence regarding the epidemiology, pathophysiology, diagnostic approach, and management of acute ischemic stroke in the paediatric population. Material and methods. A narrative review of the literature was conducted using structured searches of PubMed, Google Scholar, and clinical guideline repositories. Articles published between 2015 and 2025 were included, comprising original studies, systematic reviews, meta-analyses, and international clinical guidelines focusing on risk factors, clinical presentation, neuroimaging, acute treatment, and secondary prevention. Results. Paediatric stroke differs substantially from adult stroke in etiology, clinical features, and outcomes. The most common causes include cerebral arteriopathies, congenital heart disease, infections, and haematological disorders such as sickle cell disease. Magnetic resonance imaging is the diagnostic modality of choice, with diffusion-weighted imaging and vessel wall imaging improving diagnostic accuracy. Intravenous thrombolysis and mechanical thrombectomy may be feasible and relatively safe in selected paediatric patients; however, high-quality evidence remains limited. Conclusion. Paediatric ischemic stroke remains a diagnostic and therapeutic challenge. Delayed recognition and heterogeneous mechanisms continue to limit optimal management. Further studies are needed to develop evidence-based paediatric guidelines and improve acute and long-term outcomes.